2019
DOI: 10.1007/s13213-019-01541-z
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in microbial community composition in tannery-contaminated soil in response to increased gamma radiation

Abstract: Purpose Contaminated sites from man-made activities such as old-fashioned tanneries are inhabited by virulent microorganisms that exhibit more resistance against extreme and toxic environmental conditions. We investigated the effect of different Gamma radiation doses on microbial community composition in the sediment of an old-fashioned tannery. Methods Seven samples collected from the contaminated sites received different gamma radiation doses (I = 0.0, II = 5, III = 10, VI = 15, V = 20, VI = 25, and VII = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Particular studies are discussed below in the correspondent sections. Co γ-irradiation 0-30 kGy ↓ [103] Note: ↓-decrease, ↑-increase, or ↑↓-multidirectional changes in diversity. 1 -a range of values is provided for both background and contaminated sites; *-values were recalculated, assuming that the gamma detection rate is equal to 100%.…”
Section: Taxonomic Diversity and Structure Of Soil Communities After ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Particular studies are discussed below in the correspondent sections. Co γ-irradiation 0-30 kGy ↓ [103] Note: ↓-decrease, ↑-increase, or ↑↓-multidirectional changes in diversity. 1 -a range of values is provided for both background and contaminated sites; *-values were recalculated, assuming that the gamma detection rate is equal to 100%.…”
Section: Taxonomic Diversity and Structure Of Soil Communities After ...mentioning
confidence: 99%
“…The taxonomic structure and composition of bacterial communities often change, and their diversity significantly decreases when soils are exposed to high doses of radiation [96,99,101,103]. In such cases, the eliminated species are frequently replaced by more tolerant bacteria, fungi, or microalgae [99,101].…”
Section: Laboratory Experiments With External Irradiation Of Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, plant–microorganism–soil interaction is the main driving factor of carbon and nitrogen cycling ( Delgado-Baquerizo et al, 2016 ). Some studies have shown that a certain dose of ionizing radiation will cause changes in plant functional traits and inhibit their growth and development, changes in the content, structure, and properties of organic and inorganic substances in soil, reduction of microbial diversity, and changes in ecosystem structure and function ( Mohammad and Majed, 2019 ; Sergey et al, 2019 ; Cheptsov et al, 2021 ; Videvall et al, 2023 ). However, most of the studies on the ecological effects of ionizing radiation have mostly been carried out under laboratory conditions and usually based on a single species, excluding biological environmental factors and controlling non-biological factors, which makes these results have great limitations ( Geras'kin, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms develop resistance to radiation through adaptive reactions and can tolerate higher intensities of ionizing radiation over time (Fornalski et al, 2022). However, short-term and high-dose radiation has a sustained and irreversible impact on the composition, distribution, and metabolic pathways of microbial communities (Mohammad et al, 2019). The composition and functional integrity of biofilms are affected as the radiation causes single-strand or double-strand DNA breakages, denaturation of related proteins, and the reduction or inactivation of some enzymes (Romano et al, 2022).…”
Section: Introductionmentioning
confidence: 99%